Trends in developing economies 1993 - World Bank; World Bank. (World Bank, Washington DC., 1993)
The fifth edition of Trends in Developing Countries (TIDE) provides brief reports on most of the World Bank's borrowing member countries as of May 1993
osc 20/10/2021
Ref
Keywords: Developing economies; Economic development